A thematic analysis on Darlentina femslash as a reparative reading - Dacanay, Patricia Mae Caracas
Darna is a beloved fictional superheroine and a prominent pop culture icon in the Philippines. From just being a komiks character, she has appeared in numerous films and television adaptations throughout the years, cementing her status as a cultural icon. This study explored how Darlentina femslash-fanfiction revolving Darna's relationship with Valentina-as a reparative reading to the 2022 ABS-CBCN adaptation of Darna using Eve Sedgwick's reparative reading (2023) and Henry Jenkin's textual poaching (1992).